2023
DOI: 10.1159/000528026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Types of Hypoglycemic Medications on Psoriasis: An Analysis of Current Evidence

Abstract: <b><i>Background:</i></b> Psoriasis is a chronic recurrent inflammatory skin disease with a high risk of diabetes based on disease severity. <b><i>Objectives:</i></b> The aim of the study was to evaluate the efficacy of different hypoglycemic medications in patients with psoriasis. <b><i>Methods:</i></b> A systematic review and meta-analysis of studies were conducted to evaluate the efficacy of hypoglycemic medications in patients with pso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(93 reference statements)
1
1
0
1
Order By: Relevance
“…Additionally, a sensitivity analysis performed using a leave-one-out approach confirmed the robustness of our findings. Our meta-analysis, which had a larger sample size and included more recent studies than previous publications, 4,5 reinforces the evidence supporting the benefits of GLP-1 RAs in psoriasis treatment. Importantly, these effects extend beyond patients with psoriasis and comorbid DM.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, a sensitivity analysis performed using a leave-one-out approach confirmed the robustness of our findings. Our meta-analysis, which had a larger sample size and included more recent studies than previous publications, 4,5 reinforces the evidence supporting the benefits of GLP-1 RAs in psoriasis treatment. Importantly, these effects extend beyond patients with psoriasis and comorbid DM.…”
supporting
confidence: 81%
“…3 Two previous meta-analyses have reported that GLP-1 RAs reduce psoriasis severity. 4,5 However, their conclusions were drawn from pooled analyses comprising only two to four studies, which had mixed original study designs and included individuals without DM. Furthermore, new studies have been conducted after the publication of previous reviews.…”
mentioning
confidence: 99%
“…3 Zwei frühere Meta-Analysen haben berichtet, dass GLP-1 RAs den Schweregrad der Psoriasis verringern. 4,5 Ihre Schlussfolgerungen wurden jedoch aus gepoolten Analysen gezogen, die nur zwei bis vier Studien umfassten, deren ursprüngliche Studiendesigns uneinheitlich waren und die Personen ohne DM einschlossen. Außerdem wurden nach der Veröffentlichung der früheren Übersichten neue Studien durchgeführt.…”
unclassified